Continuous location privacy protection mechanism based on differential privacy - Hongtao LI; Xiaoyu REN; Jie WANG; Jianfeng MA (Tongxin xuebao)
Aiming at the problem of users’ location privacy leakage caused by continuously using LBS, a road privacy level (RPL) algorithm was proposed based on road topological network, which divided the privacy level of the road sections around the sensitive locations.Then, a differential privacy location protection mechanism (DPLPM) was proposed.Privacy budget was allocated for sensitive road sections and Laplace noise was added to realize the privacy protection of location data.The experimental results show that the mechanism has high data availability while protecting the privacy of location information.